Nós aqui somos um barco de aprender com o outro: redes de agroecologia na construção da autonomia camponesa - Fontes, Marilia Andrade (2019)
The agrarian issue in Brazil is unequal and contradictory. Accordingly, it advances by incorporating land, by generating capitalist relations, but also by producing - contradictorily - peasant production relations (OLIVEIRA, 1990). Martins (1981) explains that the expansion of capitalism in rural areas happens by the subjection of land income to capital, whether by the buying of land to sell or exploit, or by subordinating the peasant production. Peasants have in the fight for land the main tool for their creation and recreation (FERNANDES, 2008). There is also the fight for land that is the fight against subordination to capital, for the construction of their autonomy and the strenghthening of peasant territory. The present research-action was conducted in acting with peasants which, recreated by the fight for land, assembled an Agroecology Peasant Network as a strategy for fighting for land that drives the resistance and the confrontation against subordination to capital. The network was organized by means of exchanges of knowledge, based on the “Peasant to Peasant” methodological principles, which, according to Holt-Gímenez (2008), produce knowledge by the exchange of knowledge that ressignify the peasant lived experiences, create processes for the spreading of agroecology, guided by the horizontality and peasant protagonism. The central thesis of this work is that Agroecology Peasant Networks are capable of building up processes that contribute to peasants’ autonomy, expanding their control over their territories, thus strenghthening the fight for land. I thus elucidate the ways capital subordinates the peasants, and the strategies for constructing peasant autonomy. Moreover, the retrieval of the history of the emergence of the agroecological movement in Brazil and a theoretical discussion of agroecology constituted the starting point from which to understand and identify the processes towards autonomy driven by the Agroecology Peasant Network. This research also has the goal of analyzing whether the Agroecology Peasant Network contributed to the (re)territorialization, resistance, and expansion of autonomy and control over peasant territories in Sergipe. Deriving from this general goal are the following specific aims: (i) to describe the construction processo of the Agroecology Peasant Network by means of exchanges led by the Peasant to Peasant methodology; (ii) to identify and analyze the results/impacts of the Agroecology Peasant Network for peasant autonomy; (iii) to analyze the process of strenghthening and construction of peasant territories and of agroecology from the viewpoint of a network organization. This research-action or militant reasearch followed the methodologies of participant observantion; culture circles; and systematization of experiences. Finally, I sustain that, given the expansion of capital in rural areas, the peasants creates and recreates strategies to expand their autonomy; among them, the experience of the construction of the Agroecology Peasant Network leaves us with a lesson of the significance and centrality of peasant autonomy and its dimensions. It also points to important pathways to foster it, showing that, by means of agroecology, it is possible to expand peasant autonomy, transforming not only the relations of production, but also altering the economical, social, and political relations, strenghthening the peasant way of life and their territory.